Gambaran Workplace Well-being pada Karyawan yang Bekerja di PT X Bekasi - Zamralita; Fahlevi, Reza; Irianto, Jilly Desviona (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2024)
Human resources in a company are valuable assets because they actively contribute to the formulation and resolution of strategic issues and oversee the achievement of organisational goals. The company's human resource management must take into account the well-being of its employees. Companies that do not have optimal performance will not be able to operate effectively and efficiently. Workplace well-being is an important component that can enhance an organisation's ability to operate effectively. The work environment plays an important role in determining the well-being of employees. Factors such as the physical condition of the work environment, organisational culture, management and colleagues, and the ability to achieve a work-life balance all influence employee well-being. The concept of well-being at work refers to how employees feel about their well-being, which is the result of several characteristics of the work and office environment that cause several factors to emerge, such as safety, comfort and employee satisfaction. The purpose of this study was to determine PT X description of workplace wellbeing. This research uses quantitative methods, with 131 employees as participants. The findings showed that the workplace well-being of PT X employees was moderate (54.96%) with the highest dimension being employer care (M=4.12). Based on the findings from the study, there is no significant difference in workplace well-being based on factors such as gender, age, education level, or tenure.